New human-associated species of the family Atopobiaceae and proposal to reclassify members of the genus Olsenella. Issue 5 (28th May 2021) - Zgheib, Rita; Anani, Hussein; Meng, Marine Makoa; Mailhe, Morgane; Ricaboni, Davide; Morand, Aurélie; Caputo, Aurelia; Traore, Sory Ibrahima; Fontanini, Anthony; Armstrong, Nicholas; Raoult, Didier; Fournier, Pierre Edouard
Abstract : Five novel bacterial strains, Marseille-P1476 T (=CSURP1476 T =DSM 100642 T ), Marseille-P3256 T (=CSURP3256 T =CECT 9977 T ), Marseille-P2936 T (=CSURP2936 T =DSM 103159 T ), Marseille-P2912 T (=CSURP2912 T =DSM 103345 T ) and Marseille-P3197 T (=CSURP3197 T =CCUG 71847 T ), were isolated from various human specimens. These five strains were not identified at the species level by matrix-assisted laser desorption/ionization time of flight mass spectrometry. Following 16S rRNA gene sequence comparisons with the GenBank database, the highest nucleotide sequence similarities of all studied strains were obtained to members of the paraphyletic genus Olsenella . A polyphasic taxono-genomic strategy (16S rRNA gene-based and core genome-based phylogeny, genomic comparison, phenotypic and biochemical characteristics) enabled us to better classify these strains and reclassify Olsenella species. Among the studied strains, Marseille-P1476 T, Marseille-P2936 T and Marseille-P3197 T belonged to new species of the genus Olsenella for which we propose the names Olsenella massiliensis sp. nov., Olsenella phocaeensis sp. nov. and Olsenella urininfantis sp. nov., respectively. Strains Marseille-P2912 T and Marseille-P3256 T belonged to a new genus for which the names Thermophilibacter provencensis gen. nov., sp. nov. and Thermophilibacter mediterraneus gen. nov., sp. nov. are proposed, respectively. We also propose the creation of the genera Parafannyhessea gen. nov., Tractidigestivibacter gen. nov. and Paratractidigestivibacter gen. nov. and the reclassification of Olsenella umbonata as Parafannyhessea umbonata comb. nov., Olsenella scatoligenes as Tractidigestivibacter scatoligenes comb. nov., and Olsenella faecalis as Paratractidigestivibacter faecalis comb. nov.